2006
DOI: 10.5547/issn0195-6574-ej-volsi2006-nosi3-7
|View full text |Cite
|
Sign up to set email alerts
|

GHG Mitigation Potential, Costs and Benefits in Global Forests: A Dynamic Partial Equilibrium Approach

Abstract: This paper reports on the global potential for carbon sequestration in forest plantations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…Model (GCOMAP) (20,21), and the Global Timber Model (GTM) (22,23 To estimate the costs of reduced emissions from AD, each model must generate a baseline projection of future deforestation. The baseline is assumed to occur when AD carbon prices are $0 t Ϫ1 CO 2 .…”
Section: Marginal Cost Curves For Admentioning
confidence: 99%
“…Model (GCOMAP) (20,21), and the Global Timber Model (GTM) (22,23 To estimate the costs of reduced emissions from AD, each model must generate a baseline projection of future deforestation. The baseline is assumed to occur when AD carbon prices are $0 t Ϫ1 CO 2 .…”
Section: Marginal Cost Curves For Admentioning
confidence: 99%
“…It has been suggested that, in developing countries, the discount rate could be as high as 10%-12% as compared to 4% in developed countries [46]. Sathaye et al [47] applied a discount rate of 12%-19% for short rotation forestry in Africa and Latin America. On the other hand, Hunt [48] proposed a sustainable discount rate of 8% for the least developed countries, and Camino et al [49] used rates ranging from 4% to 16% for teak in Central America.…”
Section: Opportunity Costsmentioning
confidence: 99%
“…Sathaye (2005) describe the model as a dynamic partial equilibrium model built to simulate the response of the forestry sector to changes in future carbon prices. The general equilibrium models mostly rely on a few global data sets.…”
Section: Assessment Of Financial Incentives Using Gcomapmentioning
confidence: 99%
“…To estimate the future investment necessary for plantation implementation and the effect of those investments on the plantation rate, the Generalized Comprehensive Mitigation Assessment Process (GCOMAP) model was used (Sathaye 2005). Sathaye (2005) describe the model as a dynamic partial equilibrium model built to simulate the response of the forestry sector to changes in future carbon prices.…”
Section: Assessment Of Financial Incentives Using Gcomapmentioning
confidence: 99%